Carbonated wollastonite – An effective supplementary cementitious material?. (3rd November 2021) - Leemann, Andreas; Winnefeld, Frank; Münch, Beat; Läng, Florian
Abstract: Carbonated wollastonite clinker (CS) may be suitable as supplementary cementitious material (SCM) for mortar and concrete. The microstructure of unground CS clinker, carbonated CS slurry and a mortar blended with carbonated CS are investigated by scanning electron microscopy. Additionally, a reference mortar with pure Portland cement and one with a cement replacement level of 30 mass‐% by carbonated CS are produced to assess its contribution to compressive strength development. The calcium silicates are decalcified during carbonation resulting in CaCO3 and amorphous SiO2 . The latter reacts when used as SCM in mortar influencing the Ca/Si ratio of calcium‐silicate‐hydrate and contributing to compressive strength development.